Beta-S globin haplotypes in patients with sickle cell anemia: One approach to understand the diversity in brazil - Okumura, Jéssika Viviani [UNESP] (2013)
Universidade Estadual Paulista Júlio de Mesquita Filho - UNESP, São José do Rio Preto, S P